2015
DOI: 10.5144/0256-4947.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms are closely associated with depression in iron deficiency anemia: a comparative study

Abstract: BACKGROUND AND OBJECTIVESUntil now, very few studies evaluated the association between gastrointestinal and psychiatric symptoms in iron deficiency anemia (IDA). The study investigated the frequency of functional dyspepsia (FD) in IDA patients and determined its association with depression and somatization.DESIGN AND SETTINGSThe study was conducted at the Hematology Department of Trakya University Medical Faculty, which is a tertiary referral center in northwestern Turkey. It was a case-control study.MATERIALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Our findings in the controls are somewhat consistent with previously reported associations between IDA and depression severity as previously reported in non-psychiatric populations. 5,6 However, considering the effect sizes (all |φ| < 0.1) and the fact that, in participants with a self-reported history of IDA, 88.5% had no depression and 70.8% had a K6 score lower than the cutoff score, the association of IDA with depression risk and abnormally higher psychological distress is quite weak. Furthermore, we used the K6 test, which was not intended to evaluate depression severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings in the controls are somewhat consistent with previously reported associations between IDA and depression severity as previously reported in non-psychiatric populations. 5,6 However, considering the effect sizes (all |φ| < 0.1) and the fact that, in participants with a self-reported history of IDA, 88.5% had no depression and 70.8% had a K6 score lower than the cutoff score, the association of IDA with depression risk and abnormally higher psychological distress is quite weak. Furthermore, we used the K6 test, which was not intended to evaluate depression severity.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies reporting on iron‐deficiency anemia (IDA), which is the most common single nutritional deficiency, are limited, an association of IDA with depression severity and its relation to somatic (particularly gastrointestinal) symptoms was reported in 125 patients with IDA, compared with 57 healthy controls . Furthermore, IDA had a worsening influence on sleep quality, anxiety, and depression scores in 104 patients with IDA, compared with 80 healthy controls .…”
mentioning
confidence: 99%
“…Appropriate management of IDA is essential to avoid negative consequences and complications among vulnerable populations . Additionally, several studies showed an association between management of IDA and improvement in quality of life . The results of this study showed that more than half of patients on oral iron therapy did not show appropriate response to treatment.…”
Section: Discussionmentioning
confidence: 69%
“…25 Demir eksikliği ve depresyon şiddeti arasındaki ilişkiyi inceleyen bir başka çalışmada, 57 sağlıklı kontrolle karşılaştırıldığında, 125 anemili hastanın depresyon ve somatik semptom şikâyetleri rapor ettiği gözlemlenmiştir. 26 Semiz ise 104 anemili hastanın 80 sağlıklı hastaya kıyasla uyku kalitesi, anksiyete ve depresyon durumunda kötüleşme bildirdiğini rapor etmiştir. 27 2018 yılında 11.876 Japon vatandaş üzerinde yapılan bir çalışmada, demir eksikliği anemisi, cinsiyet ve depresyon ilişkileri incelenmiştir.…”
Section: Demi̇runclassified
“…Demirin hem yeterli diyetsel alımını hem de normal kan seviyelerinin depresyon üzerindeki olumlu etkisini gösteren birçok çalışma mevcuttur. 19,21,[23][24][25][26] Demirin yetersizliği depresyona sebep olabileceği gibi, depresyon sahibi bireylerde demir eksikliği görülme riski de fazladır. Dolayısıyla normal serum demir düzeylerinin ve diyetle yeterli demir tüketiminin, hem depresyon önleyici hem de antidepresan benzeri görev gösterdiği söylenebilir.…”
Section: Magnezyumunclassified